Detection and confirmation of various varieties of Haritaki (Terminalia chebula Retz.) in North-Western Ghats of North Karnataka - Manjunath N Ajanal; I B Kotturshetty; V S Ullegaddi (Wolters Kluwer Medknow Publications, 2019)
Background: The fruit of Myrobalan (Terminalia chebula Retz.) is considered as Amruta (Nectar) and 'King of Medicines' in Ayurveda as it has wide range of therapeutic benefits. Ayurveda has explained 7-varieties of it with botanical and pharmacological characters. Actual identification of these variety and it's botanical correlation was not done. Thus, present study was done to identify these varieties with available species of Terminalia in North-Western Ghats of North Karnataka. Methods: A prospective survey study was conducted in 10 localities of north-western Ghats of north Karnataka along with GPS system. Each identified plant and fruit was further analyzed with botanist for confirmation and collected after its maturity. The fruit was analyzed on shape, size, dimension, weight per fruit, color, mesocarp contents, seed character and size in relation with Ayurvedic classification. Further each classified fruit was analyzed on its microscopic and Powder characters etc. Results: The study identified the collected samples as Vijaya (Terminalia chebula Ver. 2 (typica)), Rohini (Terminalia chebula Ver. 3 (citrina)), Pootana (Terminalia chebula Ver. tomentella), Amirtha (Terminalia chebula Ver. gangitica) and Abhaya (Terminalia chebula Ver. parviflora, Thewaites Enum). Further, each variety has shown difference on its botanical, organoleptic, physicochemical analysis. Conclusion: The study potentially demonstrated the availability of varieties of Myrobalan in North-Western Ghats of North Karnataka and there is prominent disparity on physical and phytochemicals. Thus, it would certainly open the new pathway of research on its clinical efficacy.